Common Standards of Basal Insulin Titration in T2DM. (May 2013) - Arnolds, Sabine; Heise, Tim; Flacke, Frank; Sieber, Jochen
Type 2 diabetes mellitus has become a worldwide major health problem, and the number of people affected is steadily increasing. Thus, not all patients suffering from the disease can be treated by specialized diabetes centers or outpatient clinics, but by primary care physicians. The latter, however, might have time constraints and have to deal with many kinds of diseases or with multimorbid patients, so their focus is not so much on lowering high blood glucose values. Thus, the physicians, as well as the patients themselves, are often reluctant to initiate and adjust insulin therapy, although basal insulin therapy is considered the appropriate strategy after oral antidiabetic drug failure, according to the latest international guidelines. A substantial number of clinical studies have shown that insulin initiation and optimization can be managed successfully by using titration algorithms—even in cases where patients themselves are the drivers of insulin titration. Nevertheless, tools and strategies are needed to facilitate this process in the daily life of both primary health care professionals and patients with diabetes.